Two distinct domains of Bruno bind specifically to the oskar mRNA. - Snee, M.; Benz, D.; Jen, J.; Macdonald, P.M. (RNA Biology., 2008)
Selective deployment of Oskar protein at the posterior pole of the Drosophila oocyte relies on localization of oskar mRNA, combined with translational regulation to ensure that only the localized mRNA produces protein. The Bruno protein binds to Bruno Response Elements (BREs) in the oskar mRNA, and prevents translation of unlocalized oskar mRNA. Bruno contains three copies of the RNA Recognition Motif (RRM), a protein motif that often binds directly to RNA. Either of two nonoverlapping parts of Bruno--RRMs 1 and 2, and RRM 3 and 42 flanking amino acids--can bind specifically to BRE-containing RNA, but both domains are required for maximal binding. When expressed in Drosophila ovaries, Bruno proteins with a single RNA binding domain mutated have reduced repressive activity, while mutation of both binding domains largely eliminates this activity. Notably, the same proteins expressed as fusions to GFP accumulate in nuclei, with the most severe mislocalization occurring when both RNA binding domains are mutated. A similar mislocalization of endogenous Bruno occurs when mRNA export is blocked. Thus, Bruno shuttles between the nucleus and cytoplasm, and may first bind oskar mRNA in the nucleus.